2001
DOI: 10.1002/ps.388
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the herbicide glyphosate on non‐target spiders: Part I. Direct effects on Lepthyphantes tenuis under laboratory conditions

Abstract: We examined the toxic effects of glyphosate to adult female Lepthyphantes tenuis (Araneae, Linyphiidae), a common spider of agricultural habitats. The overspray technique was used to investigate the effect of the herbicide on forty individuals in each of six glyphosate treatments (2160, 1440, 1080, 720, 360 and 180 g ha-1) and a distilled water control. Spiders collected from the wild were individually placed in exposure chambers and checked every 24 h over a 72-h experimental period. Mortality of L tenuis rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…In an earlier experiment conducted on the long‐term study site (Section 2.2) in 1997 and published by Haughton et al ,16 it was shown that lower rates of glyphosate (90 and 180 g ha −1 ) had no significant effect on the mean total numbers of spiders 16. It was documented in the same paper that no effect on L tenuis could be detected from these glyphosate doses, and a similar result has been obtained in laboratory tests 24. The results from this experiment agree with these previous findings: only when glyphosate was applied at a dose of at least 360 g ha −1 was L tenuis affected.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In an earlier experiment conducted on the long‐term study site (Section 2.2) in 1997 and published by Haughton et al ,16 it was shown that lower rates of glyphosate (90 and 180 g ha −1 ) had no significant effect on the mean total numbers of spiders 16. It was documented in the same paper that no effect on L tenuis could be detected from these glyphosate doses, and a similar result has been obtained in laboratory tests 24. The results from this experiment agree with these previous findings: only when glyphosate was applied at a dose of at least 360 g ha −1 was L tenuis affected.…”
Section: Discussionsupporting
confidence: 91%
“…Indications are that margins which had the lowest rate of glyphosate (360 g ha −1 ) supported significantly more spiders per square metre than margins with higher rates (720 and 1440 g glyphosate ha −1 ). The chance of these differences being caused by a direct insecticidal effect is remote;24 the likelihood is that glyphosate is having an indirect habitat effect on L tenuis .…”
Section: Discussionmentioning
confidence: 99%
“…There are few reported cases of direct toxicity of glyphosate to arthropod natural enemies (Franz et al, 1997) (Brust, 1990;Haughton et al, 2001b), nor was there any apparent repellency of glyphosate to these carabid species in the greenhouse (Brust, 1990). Some evidence suggests that glyphosate may be directly toxic to at least one species of predatory mite, Neoseiulus fallacis (Garman) (Franz et al, 1997).…”
Section: Arthropod Natural Enemiesmentioning
confidence: 99%
“…Thus far, the few existing studies on terrestrial arthropods reveal few lethal effects of exposure to these herbicides (Bramble et al 1997;Giesy et al 2000;Haughton et al 2001a;Lindsay and French 2004;Michalková and Pekár 2009;Benamú et al 2010). However, the increasingly heavy use of these herbicides, facilitated by the introduction of genetically modified resistant crop plants, has contributed to the decline of agrobiont arthropod diversity in recent decades (Cane and Tepedino 2001;Benton et al 2003; Thorbek and Bilde 2004).…”
Section: Introductionmentioning
confidence: 99%